Buying and Selling of Wholesale Rice from an Islamic Economic Perspective(a Phenomenological Studi in the Urban Village Kotakulon Bondowoso) - Hastacya, Dimas Jovanka; Saleh, Mohammad; Amijaya, Rachmania Nurul Fitri; Lutfiani, Hilda (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2024)
Sale and purchase that most often deviates from Islamic economics is the piecework system, one of which is the sale of agricultural crops. Deviations from Islamic economics in wholesale buying and selling transactions result in the risk of loss that must be borne by one of the parties involved, both the seller (farmer) and the buyer (contractor). The purpose of this research is to find out the factors that influence farmers in Kotakulon urban village Bondowoso to buy and sell rice in bulk, to find out the practice of buying and selling rice in bulk carried out in Kotakulon urban village Bondowoso and to find out whether buying and selling in bulk in Kotakulon urban village Bondowoso Village is in accordance or not with the perspective of Islamic economics (Maqashid sharia). This research uses a qualitative approach with phenomenological methods. Meanwhile, the data collection techniques used are observation, interviews, and documentation. The informants in this study consisted of farmers and contractors. The analysis method used is data reduction, data presentation and conclusion drawing or verification.The results of this study indicate that from the point of view of maqashid sharia theory on the practice of the wholesale system if green rice is traded as a whole, the practice of buying and selling rice by wholesale involving modern technology, fairness in pricing, flexibility in payment, and trust between the parties involved is a practice that can be in line with the five main elements of maqashid sharia as long as it complies with Islamic law.